EXPLORING THE SELF-CONFIDENCE OF SIXTH SEMESTER STUDENT PRESENTING PROPOSAL DURING THE PROPOSAL SEMINAR COURSE - Kristina, Geofani; Novelita, Naomi Mars; Panjaitan, Angels Dermika; Monika, Tiara; Zahara, Nasyiva; Situmorang, Citra Betha; Dewi, Desi Surlitasari; Manurung, Sulastri; Susanti, Ervin Nora; Sirait, Sindy Deswita Natalia (Universitas Riau Kepulauan, 2024)
This study aims to explore sixth semester students' self-confidence in presenting research proposals in the Proposal Seminar course. Using a mixed methods approach, data was obtained from 19 students through a self-confidence questionnaire and semi-structured interviews. The questionnaire results showed that most participants had a high level of self-confidence, with an average score of 79.61%. Analysis of the interview transcripts revealed six main themes: strengths in presenting, presentation challenges, preparedness, coping strategies, audience influence, and self-reflection. Although many students experienced nervousness, they demonstrated an awareness of their strengths and applied strategies such as deep breathing, positive thinking, and rehearsal as ways to manage anxiety. The presence of an evaluative audience, especially lecturers, proved to be a major influence on students' confidence levels. Overall, the results show that students' self-confidence is dynamic and shaped by readiness, experience, audience context, and reflective practice. This study emphasizes the importance of a supportive academic environment to foster confidence in oral academic presentations.